Ethical environmental governance, public participation and sustainable development in the EIA decision-making process : a case study of the Xolobeni Heavy Mineral Sands project - Xala, Xolela (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2023.